Frequency of Umbilical Port Site Infection after Cholecystectomy: A Single Centre Cross-Sectional Study - Bezan Baloch, Saleem Javed, Azizullah Khan Sherani, Muhammad Idrees Achakzai, Mehmood Ali, Saiqa Rafiq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Laparoscopic surgery may be used to treat cholelithiasis, pancreatic inflammation, gallbladder stones, and gallbladder tumours, often known as polyps. Due to its safety and status as the gold standard, gallbladder resection combined with a laparoscopic cholecystectomy is regarded as the preferred surgical procedure. Objective: To determine the frequency of umbilical port site infection after cholecystectomy Study Design: Descriptive cross-sectional study Place and study duration: The current study was done at the Surgery Department, BMC/Bolan Medical Complex Hospital Quetta for a period of six months from Feb 2023 to July 2023. Methods: The study was approved from the ethical committee of the hospital. A total of 100 patients participated in our study. Data were acquired by observing patients and laboratory reports; furthermore, the analysis was conducted using the newest version of SPSS 24. Results: In our study, totally 100 patients were selected. The mean age of the patients was. The mean age of the enrolled patients was 42 (11.2) years with minimum age of 20 and maximum age of 70 years. The male patients in our study were 42 (42%) and females were 58 (58%). The frequency of port site infection after cholecystectomy was 15 (15 %). The most common of infection was umbilical port site in 9 (60 %) followed by epigastric infection in 4 (26.67 %) patients, suprapubic infection in 1 (6.67 %) patient and Palmer’s point infection in 1 (6.67 %) patient. Conclusion: Our study concludes that port site infection after cholecystectomy is a common problem. The most common complication after cholecystectomy in our study was umbilical port site infection followed by epigastric infection. Consequently, this may be reduced with appropriate aseptic methods and postoperative patient care. Keywords: laparoscopy; cholecystectomy, post-surgical infection; suprapubic infection